PENGARUH MOTIVASI DAN BUDAYA ORGANISASI TERHADAP KINERJA GURU SEKOLAH MENENGAH PERTAMA (STUDI KASUS PADA SMPN 252 JAKARTA TIMUR) - Dahlia Sarkawi (Cakrawala - Jurnal Humaniora, 2009)
The achievement of the point of view, the mission and the aim of the school that was maintained together by the pupil, was needed by the condition for the conducive school and the harmony between the available educational power in the school including the principal, the teacher, the administrative power, and parents of the pupil, as well as their respective community had the role that was big enough in achieving the aim of the organisation. The teacher's power was one of the educational powers that had the role as the determining factor of the success of the aim of the organisation apart from the other educational power, because of the direct teacher bersinggungan with participants educated, to give the guidance that his estuary will produce the graduate who was hoped for. So the achievement of the teacher must be always increased. Efforts to increase the achievement usually were carried out by means of giving the motivation, held the supervision, gave the incentive, gave the opportunity that was good for developed in the career, increased the capacity, the style of good leadership. While the achievement of the teacher could be increased if that was relevant knew what was hoped for and when could determine hopes that were acknowledged by results of his work. Key word:  motivation,  organisation culture and achievement